The Oxford dictionary of music - Kennedy, Michael, 1926-2014; Kennedy, Joyce Bourne (Oxford paperback reference., 2013)
This quick reference book of musical terminology includes brief biographical sketches of musicians, composers, vocalists, and conductors.